Evaluation of a novel chemiluminescent immunoassay for autoantibody detection in pemphigus and bullous pemphigoid - Zhang, Na; Wang, Ming; Hou, Lili; Zhang, Yanyu; Zhao, Yan; Du, Luyang; Li, Xiaoqing; Liu, Xia; Zhou, Hongwei; Hao, Jiaxuan; Tian, Jing; Yu, Qiuping; et al. (Frontiers in Immunology, 2025)
BackgroundA novel fully automated chemiluminescent immunoassay (CLIA) has been developed to quantify autoantibodies specific for desmogleins (Dsg1, Dsg3), BP180, and BP230, key target antigens in pemphigus and bullous pemphigoid. This study aims to evaluate the diagnostic accuracy of the CLIA in diagnosing pemphigus and BP and its correlation with disease severity and clinical features.MethodsSera from 106 bullous pemphigoid and 54 pemphigus patients and control sera from 153 patients with other skin disease and 121 healthy volunteers were included. CLIA and BIOCHIP mosaic-based indirect immunofluorescence (IIFT-BIOCHIP) were performed for all bullous pemphigoid and pemphigus patients, with ELISA conducted for most. Disease severity was assessed using the Body Surface Area scoring.ResultsThis CLIA showed strong agreement with IIFT-BIOCHIP, achieving area under the curve (AUC) values of 0.92 for anti-Dsg1/anti-Dsg3 and 0.84 for anti-BP180/anti-BP230 for differentiating pemphigus and BP. It outperformed ELISA (AUC: 0.73, 0.75) and was comparable to IIFT-BIOCHIP (AUC: 0.93, 0.87). The assay showed superior detection range and sensitivity compared to ELISA. Autoantibody levels correlated with disease severity and clinical symptoms, with elevated levels of anti-Dsg3 associated with mucosal lesions, anti-Dsg1/anti-Dsg3 associated with Nikolsky sign, and elevated anti-BP180/anti-BP230 levels linked to pruritus.ConclusionsThe novel CLIA, the first to quantify four major autoimmune blister disease autoantibodies (anti-Dsg1/anti-Dsg3/anti-BP180/anti-BP230) using a single sample tube, offers a simple and time-efficient test for diagnosing and screening pemphigus and BP. Its ability to assess disease severity and clinical relevance makes it a valuable tool for managing these conditions.